The Theatrics of the Auto de amores in the Tragicomedia called Celestina - Peter Cocozzella (Celestinesca, 2021)
The auto de amores is a little-known theatrical genre —a  mini-play  of  sorts— which epitomizes the love-centered literature in vogue both in the Castilian and the Catalan domains throughout the fifteenth century. A review of the few extant specimens of the auto in question may serve as a basis for a fresh approach to the Tragicomedia de Calisto y Melibea. Demonstrably, the auto de amores is eminently suited to representation on the stage particularly as embodiment of an exemplum. The present study consists of two parts. The first underscores the modular qualities of the auto in question —especially its essential theatricality, compactness, and adaptability— as a key component of the Tragicomedia. The second part explores the ways in which the modular auto is assimilated into a composition of complex design and major proportion